A Struggle to Keep Environmental Protests Above Party Politics: The Cerattepe Case - Busra Soylemez-karakoc; Mesut Karakoç (Alternatif Politika)
The Cerattepe mining project for the extraction of gold and copper in the city of Artvin has been controversial since the mid-1980s. Local resistance against the project peaked in 2015-2016 in the form of blockages, sit-ins, social media protests, litigations, and signed petitions. This paper analyzes protests against the Cerattepe mining project in terms of their motivations, strategies, limitations, and political perceptions. Through an original survey analysis (N=253) and interview data, we find that the locals frame their activism as above party politics to keep a legitimate position in resisting the mining project. This strategy has remained intact for several years despite the politicization attempts of resistance from national-level political parties. We explain this strategy with the national consensus on prioritizing economic growth over environmental issues, neoliberal developmentalism with strong state support for private companies, and high levels of political polarization in society. Overall, the study offers an understanding of the challenges in front of environmental issue-based activism in Turkey and reveals the strategies of locals in resisting an environmentally destructive mining project.